2020
DOI: 10.1021/acs.iecr.0c02695
|View full text |Cite
|
Sign up to set email alerts
|

A Urea-Functionalized Chemoreceptor for Expeditious Chromogenic Recognition of Toxic Industrial Pollutants Cu2+ and CN from Real Water Sources and Biofluids: Diagnosis of Wilson’s disease from Human Urine

Abstract: A urea-functionalized chemoreceptor 1,5-bis(2,4dinitrophenyl)carbonohydrazide (BDC) with versatile applications has been reported in this work. BDC displayed ditopic sensitivity toward toxic industrial pollutants Cu 2+ and CN − from a purely aqueous medium. BDC has been structurally authenticated by ESI-MS, 1 H-NMR, FT-IR, and SCXRD. It can undergo promising "naked eye" detection in the existence of the targeted analytes (pale yellow to dark purple for Cu 2+ and pale yellow to dark brown for CN − ) in the sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Thus, it could be predicted that NAP-1 maintains 1:1 binding stoichiometry with Cu 2+ . The corresponding association constant for 1:1 binding stoichiometry was obtained to be 2.34 × 10 8 M –1 from the Benesi–Hildebrand equation (Figure S24, SI). To investigate the response rate of NAP-1 toward Cu 2+ , a time-dependent study has been carried out using Cu 2+ of different concentrations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, it could be predicted that NAP-1 maintains 1:1 binding stoichiometry with Cu 2+ . The corresponding association constant for 1:1 binding stoichiometry was obtained to be 2.34 × 10 8 M –1 from the Benesi–Hildebrand equation (Figure S24, SI). To investigate the response rate of NAP-1 toward Cu 2+ , a time-dependent study has been carried out using Cu 2+ of different concentrations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Banerjee et al described urea-based probe 6, which displayed discriminative chromogenic changes from pale yellow to dark purple for Cu 2+ . 34 6 displayed a sub-nanomolar detection threshold (46 Â 10 À8 M) in purely aqueous medium. With the steady addition of Cu 2+ to 6, the initial peak of 6 (335 nm) was diminished with the synchronous generation of a new peak at 550 nm, rationalizing a plausible CT from the filled molecular orbital of 6 towards the vacant d 9 orbital of Cu 2+ via the ligandto-metal charge transfer phenomenon (LMCT).…”
Section: Intramolecular Charge Transfer (Ict)-based Sensory Probesmentioning
confidence: 99%
“…Banerjee et al revealed that urea-based probe 6 34 exhibited a distinct “naked-eye” response towards CN − in purely aqueous medium with a detection threshold of 92 × 10 −9 M. The ICT and intermolecular H-bonding interaction between the –NH and –CH protons in 6 with the target CN − analyte was rationalized as the underlying recognition phenomenon. 6 displayed reversibility with alternating CN − and Cd 2+ , which served as an absolute and reliable platform towards mimicking a molecular logic gate-based ensemble (Fig.…”
Section: Chromo-fluorogenic Probes For the Detection Of Cn−mentioning
confidence: 99%
“…L1 displayed four signals at 220, 250, 325 with a broad signal at 415 nm due to π-π*, n-π* and charge transfer transition within the framework respectively. The absorption spectra of L1 in acetonitrile: HEPES (4 : 1, v/v, conc n : 2 × 10 À 5 M, pH 7.4) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (λ max /nm; ε/M À 1 cm À 1 ): 325 (18100) and for L1-Zn 2 + (λ max /nm; ε/M À 1 cm À 1 ): 370 (11100) respectively (Figure S5a-b). Photoexcitation at 400 nm gives fluorescence of L1 (conc n : 5 × 10 À 6 M, pH 7.4) at 495 nm which reveals a Stokes Shift of 80 nm.…”
Section: Metal Binding Studymentioning
confidence: 99%